2000
DOI: 10.1021/ma992103b
|View full text |Cite
|
Sign up to set email alerts
|

Complex Formation of Poly(ε-caprolactone) with Cyclodextrins

Abstract: Cyclodextrins (CDs) have been found to form inclusion complexes with poly(ε-caprolactone) (PEC) to give crystalline compounds. α- and γ-CD formed complexes with these polyesters in high yields, although β-CD gave complexes in moderate yields. The yields of the complexes decreased with increasing molecular weight of the polymer. α-CD−PEC complexes are stoichiometric one-to-one (cyclodextrin:monomer unit) compounds, and γ-CD−PEC complexes are one-to-two compounds when the molecular weights of PEC are low. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
150
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 160 publications
(159 citation statements)
references
References 55 publications
(54 reference statements)
5
150
0
2
Order By: Relevance
“…The b-CD and the IL can promote the solubility of each other due to the soluble nature of the ICs formed. XRD, 13 C CP/MAS NMR, and TGA studies illustrated that the ICs are isomorphous, with a channel-type structure, with the b-CD molecules adopting a symmetrical conformation, and with each glucose unit of b-CD being in a similar environment. The thermal stability of the ICs is lower than the two precursors.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The b-CD and the IL can promote the solubility of each other due to the soluble nature of the ICs formed. XRD, 13 C CP/MAS NMR, and TGA studies illustrated that the ICs are isomorphous, with a channel-type structure, with the b-CD molecules adopting a symmetrical conformation, and with each glucose unit of b-CD being in a similar environment. The thermal stability of the ICs is lower than the two precursors.…”
Section: Resultsmentioning
confidence: 99%
“…The solubility and conductivity results indicated that inclusion complexes (ICs) of 1:1 stoichiometry were formed. The inclusion compounds were further characterized by using powder X-ray diffraction (XRD) analysis, 13 C CP/MAS (cross-polarization magicangle spinning) NMR and 1 H NMR spectroscopy, and thermogravimetric analysis (TGA). The results showed that the ICs were a fine crystalline powder.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations